Pengaruh Laju Pertumbuhan Ekonomi, Inflasi dan BI Rate Terhadap Tingkat Pengagguran Terbuka di Indonesia - Anjel Ezania Sihombing; Adyanto Armando Purba; Nur Indah; Tri Kurnia; Revita Yuni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to determine the rate of economic growth, inflation and BI rate simultaneously and partially on the level of open unemployment in Indonesia in the period 2003 - 2022. Where unemployment is the dependent variable while the rate of economic growth, inflation, and interest rates are independent variables. This research uses time series data with the method used in this research is quantitative descriptive analysis, using multiple regression analysis tools and processed through eviews. .data comes from Bank Indonesia and the Central Statistics Agency (BPS). The results of this research show 1) LPE has a negative and significant effect on unemployment 2) The inflation variable has no effect on the level of open unemployment in Indonesia 3) The interest rate variable (Bi Rate) has a positive and significant effect on the level of open unemployment in Indonesia.